The Spanish block of the ESCB-multi-country model - Alpo Willman; Ángel Estrada (European Central Bank (ECB), 2002)
This paper presents the Spanish country block (ES-MCM) of the ESCB Multi-Country Model for the euro area, which has been built in a close co-operation with the ECB and the Banco de Espaa. The theoretical structure of the ES-MCM block is in line with most current mainstream macro models, i.e. the supply factors determine the long-run equilibrium, while in the short run output is demand-determined, resulting from a sluggish adjustment of prices and quantities. The paper is structured as follows. First, a simplified theoretical counterpart of the ES-MCM block is presented and its steady-state comparative statistics and stock-flow equilibrium properties are studied. The theoretical analysis is followed by the review of the estimated equations of the ES-MCM block. Finally the simulation properties of the ES-MCM block are presented in the light of five alternative shock simulations.
Keywords: E10; E13; E17; 330